2021
DOI: 10.1126/scitranslmed.abi4547
|View full text |Cite
|
Sign up to set email alerts
|

Protective antibodies elicited by SARS-CoV-2 spike protein vaccination are boosted in the lung after challenge in nonhuman primates

Abstract: Adjuvanted soluble protein vaccines have been used extensively in humans for protection against various viral infections based on their robust induction of antibody responses. Here, soluble prefusion-stabilized spike protein trimers (preS dTM) from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were formulated with the adjuvant AS03 and administered twice to nonhuman primates (NHP). Binding and functional neutralization assays and systems serology revealed that the vaccinated NHP developed AS03-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

6
4

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 102 publications
3
46
0
Order By: Relevance
“…Avidity was measured as described previously (Francica et al, 2021) in an adapted ELISA assay. Briefly, ELISA against S-2P was performed in the absence or presence of sodium thiocyanate (NaSCN) and developed with HRP-conjugated goat anti-monkey IgG (H+L) secondary antibody (Invitrogen) and SureBlue 3,3′,5,5′-tetramethylbenzidine (TMB) microwell peroxidase substrate (1-Component; SeraCare) and quenched with 1 N H 2 SO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Avidity was measured as described previously (Francica et al, 2021) in an adapted ELISA assay. Briefly, ELISA against S-2P was performed in the absence or presence of sodium thiocyanate (NaSCN) and developed with HRP-conjugated goat anti-monkey IgG (H+L) secondary antibody (Invitrogen) and SureBlue 3,3′,5,5′-tetramethylbenzidine (TMB) microwell peroxidase substrate (1-Component; SeraCare) and quenched with 1 N H 2 SO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have combined the soluble prefusion-stabilized S trimers (preS dTM) from SARS-CoV-2 with the adjuvant AS03 and injected it twice into NHPs. Results suggest that the IgG antibodies induced by this adjuvanted vaccine can protect NHPs against SARS-CoV-2 infection [33]. Similarly, interim results from a randomized, placebo-controlled phase 1-2 dose-range study in healthy adults demonstrated that the preS dTM vaccine adjuvanted with AS03 has effectively promoted the production of anti-virus neutralizing antibodies [34].…”
Section: Oil-in-water Emulsion Adjuvantsmentioning
confidence: 82%
“…Our studies with NTD-scNP immunization demonstrated neutralizing antibodies may not be the only mediators of protection. While the RBD subunit has been shown to protect against SARS-CoV-2 challenge in animal models (Dai et al, 2020; Francica et al, 2021; Pino et al, 2021; Saunders et al ., 2021; Yang et al, 2020), the NTD is also an immunodominant region for neutralizing antibodies (Cerutti et al, 2021; Chi et al, 2020; Li et al ., 2021a; Martinez et al, 2021b; McCallum et al, 2021; Voysey et al, 2021). However, NTD is the site of multiple mutations and NTD antibody neutralization is, in general, less potent than RBD antibodies.…”
Section: Discussionmentioning
confidence: 99%